2023
DOI: 10.1038/s42003-023-04772-8
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic data and structure analysis combined reveal interplay of structural rigidity and flexibility on selectivity of cysteine cathepsins

Abstract: Addressing the elusive specificity of cysteine cathepsins, which in contrast to caspases and trypsin-like proteases lack strict specificity determining P1 pocket, calls for innovative approaches. Proteomic analysis of cell lysates with human cathepsins K, V, B, L, S, and F identified 30,000 cleavage sites, which we analyzed by software platform SAPS-ESI (Statistical Approach to Peptidyl Substrate-Enzyme Specific Interactions). SAPS-ESI is used to generate clusters and training sets for support vector machine l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 69 publications
0
3
0
Order By: Relevance
“…Recently, proteomics-based screening of peptidyl substrates of the cysteine cathepsins B, F, K, L, S, and V revealed that CatL positions from P1 to P3 and P1′ are specific for substrate binding, preferably hydrophobic residues. 17 The P2 residue points into the protein and has exceptional preference for nonpolar groups due to the shape of the hydrophobic S2 subsite. The P1 residue has no obvious contact with the protein surface and has the additional probability of tolerating polar uncharged groups.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, proteomics-based screening of peptidyl substrates of the cysteine cathepsins B, F, K, L, S, and V revealed that CatL positions from P1 to P3 and P1′ are specific for substrate binding, preferably hydrophobic residues. 17 The P2 residue points into the protein and has exceptional preference for nonpolar groups due to the shape of the hydrophobic S2 subsite. The P1 residue has no obvious contact with the protein surface and has the additional probability of tolerating polar uncharged groups.…”
Section: Discussionmentioning
confidence: 99%
“…It prefers combinations of hydrophobic residues at the P3 and P2 positions. Several amino acid combinations favor positively charged residues at P1 and P1′ positions. , The common Schechter and Berger nomenclature of S and P subsites of protease active sites will be used consistently herein.…”
Section: Introductionmentioning
confidence: 99%
“…The binding sites between the substrate and enzyme are the S2, S1, and S1 sites [29]. Moreover, a combined approach including proteomics data and a structural analysis enabled the recognition of crucial regions and residues within cysteine cathepsins, which endow them with specific properties, thus highlighting an interplay between structural rigidity and flexibility on selectivity [30]. Very recently, a clustering of papain-like cysteine proteinases based on profile-profile mappings has shown structural conservation in addition to a well-preserved catalytic triad and oxyanion hole [31].…”
Section: Introductionmentioning
confidence: 99%